THE EFFECT OF DEEP BREATHING RELAXATION IN DECREASING THE PRAGNANCY WOMEN ANXIETY OF PRIMIGRAVIDATHIRD TRIMESTER IN FACING THE CHILDBIRTH PROCESS WORK AREA HEALTH CENTER OF TALANG RIMBO LAMA REJANG LEBONG BENGKULU - Kurniyati; Bakara, Derison Marsinova (JURNAL KESEHATAN ALMUSLIM, 2018)
Pregnancy is a transitional period in a woman’s life process with physiological, cognitive, emotional, and social alterations;therefore pregnant women frequently worry about pregnancy and childbirth that will have a serious risk. This research is aimed to know the influence of breathing relaxation toward the decreasing of anxiety in primigravida trimester III work area of Talang Rimbo Lama Rejang Lebong Health Center. The population in this study was pregnant primigravida trimester III. The Sample was 38 people. The Instruments used were Hamilton Rating Scale for Anxiety (HRSA) and the observation form for the step of deep breath relaxation technique. The research method used was Quasi Experimental;pre test and post test design with control group or a research design in measuring cause and effect.This research investigated the intervention of breathing relaxation at trisemster pregnant women in facing the childbirth process. The result of the research proved that there is an effect of breathing technique in the reduction of the anxiety in pregnant women of trisemester III in facing the childbirth with P <0,05. Conclusion: There is an effect of breathing technique regarding the decreasing of anxiety in pregnant women primigravida trimester III while facing the childbirth.